Sensitive and label-free fluorescent microRNA detection via catalytic DNAzyme assembly initiated primer exchange reaction - Heng Wang; Yi Sun (Results in Chemistry)
MicroRNAs (miRNAs) have an intricate connection to the development of human diseases, such as malignancies, diabetes, and viral infections; therefore, their rapid and precise identification is critical in disease diagnosis and treatment. In this study, we have developed an innovative technique for detecting miRNA using a highly sensitive and label-free fluorescence approach. This method combines the target recognition-based catalytic hairpin assembly (CHA) driven DNAzyme system with the primer exchange reaction (PER). This method involves three signal amplification processes: CHA-based target recycling, DNAzyme-based signal amplification, and PER, which endow the method with a high sensitivity. Furthermore, a block sequence has been incorporated into the template probe for PER, resulting in a substantial decrease in interferences caused by non-specific targets. Finally, the created G-quadruplex can fix thioflavin T (ThT) to generate fluorescence signals in a label-free manner. Based on this, the approach demonstrates a high miRNA detection sensitivity with a low limit of detection of 0.32 fM. Furthermore, this approach effectively identified miRNA-21 in cellular extracts, thereby showcasing its exceptional resistance to interference. The suggested technology utilizing G-quadruplex/ThT offers intrinsic advantages that make it suitable for widespread application in bioanalysis and early identification of illnesses.